Expanding the boundaries: regional connectivity in green turtle (Chelonia mydas) populations across Micronesia - Jensen, Michael P.; LaCasella, Erin L.; Kobayashi, Donald R.; Frey, Amy; Summers, Tammy M.; Hapdei, Jessy R.; Balazs, George H.; Murakawa, Shawn K. K.; Jones, T. Todd; Martin, Summer L.; Gaos, Alexander R.; Dutton, Peter H. (Frontiers in Marine Science, 2025)
The importance of ocean currents in influencing the connectivity and dispersal of marine megafauna, including sea turtles, is becoming increasingly recognized. However, more comprehensive studies are needed on how these currents impact the genetic makeup and connectivity of green turtle Chelonia mydas (Linnaeus, 1758) populations in the Pacific Islands region. To address this gap, our study conducted genetic analyses of green turtles in foraging grounds from four Micronesian sites and predictive modelling of hatchling dispersal patterns based on ocean currents to explore connectivity between foraging grounds and rookeries across Micronesia. We analyzed mitochondrial DNA (mtDNA) haplotype frequencies from newly collected and published data. We used Bayesian mixed stock analysis (MSA) to estimate the relative proportion of turtles from different Management Units (MUs) within the foraging grounds. Our ocean current simulations predicted hatchling dispersal trajectories, revealing how passive drift may facilitate wide-ranging dispersal and connectivity among distant foraging and nesting sites. Across the four Micronesian foraging grounds, the MSA revealed varying contributions from different rookeries, with some turtles exhibiting rare, long-distance dispersal traits. Our study highlights the intricate relationship between oceanic currents and the spatial dynamics of green turtles across the Pacific. Our findings offer essential insights into the conservation and management of green turtles by highlighting the role of oceanic currents in shaping population connectivity. Future research should focus on expanding genetic analyses and refining ocean drift simulations to enhance our understanding of marine megafauna migration and inform regional conservation strategies effectively.